Research on Innovative Design of Velvet Flowers as an Intangible Cultural Heritage from a Semiotic Perspective - Tao Jiang (Textile & Leather Review)
This study investigates the innovative pathways for integrating velvet flowers, as an element of intangible cultural heritage (ICH), into modern design. Utilizing a semiotic three-dimensional framework (syntactic, semantics, pragmatics), the study deconstructs and reconstructs the cultural symbols of velvet flowers, aiming to merge traditional craftsmanship with contemporary aesthetics. Through an analysis of the selection, reconstruction, and transformation of meanings within velvet flower symbols, this paper proposes a strategy for converting traditional symbols into a design language that aligns with modern aesthetic values and market demands. The case studies demonstrate how velvet flower symbols retain cultural significance while adapting to the diverse demands of the contemporary market. The findings indicate that the selection and reconstruction of symbols, as well as the extension and transformation of their meanings, are key steps in the innovative design of velvet flowers. Furthermore, by comparing cross-cultural innovation cases, the study highlights the global market potential and cultural adaptability of velvet flower design, with particular attention to market prospects in various regions. The research also examines commercialization strategies, including cross-disciplinary collaboration, brand partnerships, and sustainable development, to expand market reach and enhance brand influence. In conclusion, this study provides a theoretical framework and practical guidance for the modernization and global dissemination of velvet flower craftsmanship.